Development of chimeric lysins to elucidate the utility of sortase directed enzybiotics - Newman, Robert (2020)
The ability to provide prophylaxis and curative treatment of bacterial infections through the use of antibiotics has become a fundamental pillar of modern medicine. As such, the threat antibiotic resistance poses is of major concern for global health organizations and populations. Pathogenic strains of the commensal Gram-positive bacterium Staphylococcus aureus are a common cause of nosocomial infections, with their treatment and management being complicated by the increased prevalence of methicillin and multidrug resistance strains. With few new antibiotics on the horizon and their fate likely to reflect that of their predecessors, it poses the question of what alternatives approaches are available. One such approach is the targeting of the cell wall of S. aureus and other Gram-positive bacteria with peptidoglycan digesting enzymes. Exploiting the specificity, modularity and diversity of peptidoglycan hydrolases allows for the selective targeting of the highly conserved peptidoglycan of different Gram-positive species. Key to this approach is the reliable and specific targeting of catalytic domains to the cell wall. As such, this project sought to express and purify eGFP reporter fusions for future use in microscopy and binding assays to evaluate the cell wall anchoring ability of the endogenous Sortase A upon exogenous sort-tagged proteins. To this end we report the successful expression and purification of both SH3b and sort-tagged eGFP fusions despite the occurrence of truncation products stemming from the differing codon usage of its source. An issue also identified with the sequence of Lysostaphin fragments which will be considered in future work. We also report the generation of a DNA construct library, encoding chimeric lysins which will be used in future studies comparing the relative staphylolytic activity of different peptidoglycan hydrolase catalytic domains when fused to either a staphylococcal sort-tag or the cell wall binding domain of Lysostaphin.